Optimizing a multifunctional microsphere scaffold to improve neural precursor cell transplantation for traumatic brain injury repair. (9th October 2013) - Skop, Nolan B.; Calderon, Frances; Cho, Cheul H.; Gandhi, Chirag D.; Levison, Steven W.
Abstract: Tissue engineering using stem cells is widely used to repair damaged tissues in diverse biological systems; however, this approach has met with less success in regenerating the central nervous system (CNS). In this study we optimized and characterized the surface chemistry of chitosan‐based scaffolds for CNS repair. To maintain radial glial cell (RGC) character of primitive neural precursors, fibronectin was adsorbed to chitosan. The chitosan was further modified by covalently linking heparin using genipin, which then served as a linker to immobilize fibroblast growth factor‐2 (FGF‐2), creating a multifunctional film. Fetal rat neural precursors plated onto this multifunctional film proliferated and remained multipotent for at least 3 days without providing soluble FGF‐2. Moreover, they remained less mature and more highly proliferative than cells maintained on fibronectin‐coated substrates in culture medium supplemented with soluble FGF‐2. To create a vehicle for cell transplantation, a 3% chitosan solution was electrosprayed into a coagulation bath to generate microspheres (range 30–100 µm, mean 64 µm) that were subsequently modified. Radial glial cells seeded onto these multifunctional microspheres proliferated for at least 7 days in culture and the microspheres containing cells were small enough to be injected, using 23 Gauge Hamilton syringes, into the brains of adult rats that had previously sustained cortical contusion injuries. When analysed 3 days later, the transplanted RGCs were positive for the stem cell/progenitor marker Nestin. These results demonstrate that this multifunctional scaffold can be used as a cellular and growth factor delivery vehicle for the use in developing cell transplantation therapies for traumatic brain injuries. Copyright © 2013 John Wiley & Sons, Ltd.